Effects of Surface Waviness on the Nonlinear Vibration of Gas Lubricated Bearing-Rotor System - Jian Li; Shaoqi Yang; Xiaoming Li; Qing Li (Shock and Vibration)
This paper presents the effects of the surface waviness on the nonlinear dynamic performance of a gas bearing-rotor system. The coupled vibration with the elastomer is taken into consideration to fit the actual engineering application. The effects of the directions, the amplitudes, and the numbers of waves to the nonlinear dynamic performance are investigated. The results show that the existence of the surface waviness in the circumferential direction can improve the stability of the system obviously. But the surface waviness in the axial direction is damage to the system. The nonlinear dynamic performance of the system is insensitive to the number of surface waviness. The increase of the amplitude of the waviness in circumferential direction can improve the stability of the system.